MO174FIBROSCAN DETECTION OF FATTY LIVER AND LIVER FIBROSIS IN SYSTEMIC LUPUS ERYTHEMATOSUS. (29th May 2021) - Yetginoglu, Ozge; Barutcu Atas, Dilek; Velioglu, Arzu; Arıkan, İzzet Hakkı and Yilmaz, Yusuf and Alibaz Oner, Fatma and Direskeneli, Haner and Tuglular, Z Serhan and Asicioglu, Ebru
Abstract: Background and Aims: Systemic Lupus Erythematosus (SLE) is a chronic, multi-organ, systemic autoimmune disease that is more common in women than men and is typically diagnosed during the reproductive age. Although liver dysfunction is not considered the main organ pathology in SLE, the frequency of liver dysfunction or abnormal liver enzyme values may be observed in 50-60% of patients. Liver-related complications may present as asymptomatic hepatomegaly, subclinical steatosis and abnormal liver enzymes. The most common causes are drug-associated liver injury, lupus-associated hepatitis, and fatty liver disease. The aim of this study was to assess fatty liver and liver fibrosis in SLE patients using the FibroScan method as well as associated factors such as immunosuppressive medications. Method: Sixty SLE patients and 30 healthy controls were included. Patients with HBV, HCV or cirrhosis, malignancy, cardiac disease, or patients on dialysis were excluded. All participants underwent FibroScan measurements. Demographic data and cumulative doses of immunosuppressive medications were extracted from patient charts. Fasting blood was collected for analysis Results: Demographic and clinical characteristics of the study groups are shown in Tables 1. The prevalence of fatty liver disease was similar between SLE patients and healthy controls (21.7% vs 26.7%, p= 0.597) and was associated with body mass index (BMI) (p= 0.026) and C-reactive protein (CRP) (p= 0.046) in multivariate analysis. Liver fibrosis was also similar between the two groups (26.7% vs 10.0%, p= 0.069). There was no relationship between cumulative drug doses including glucocorticoids with either fatty liver disease or liver fibrosis. Since the majority of SLE patients were female, we performed a subgroup analysis in female patients (n=51) and healthy controls (n=25). Fatty liver disease was similar between female SLE patients and healthy controls (23.5% vs 24.0%, p= 0.964). However, liver fibrosis in female patients with SLE was increased compared to the female healthy population (29.4% vs 4.0%, p= 0.011) and was associated with age (p= 0.034) and low-dose cumulative glucocorticoid use (p = 0.034). Low-dose cumulative glucocorticoid use was defined as less than 17.45 g, which was the 75th percentile value. Only 1 out of 15 female patients with fibrosis had high-dose cumulative glucocorticoid use (>17.45 g), while the remaining 14 patients had used lower doses (<17.45 g). Conclusion: The prevalence of fatty liver was similar between SLE patients and healthy controls, while liver fibrosis was increased in the female patient group as compared to controls. Furthermore, liver fibrosis was associated with age and low dose cumulative glucocorticoid use. Interestingly, fatty liver did not precede liver fibrosis in the majority of cases, contrary to what is observed in the general population. We hypothesized that liver fibrosis may be the result of subclinical inflammation and autoimmunity associated with SLE itself and the use of steroids may prevent or prolong fibrosis formation in the liver.